Influence of weather factors on the abundance and population dynamics of Spodoptera litura F. and Pieris brassicae L. on cabbage (SAARC Journal of Agriculture, 2017)
In order to study the influence of weather factors on the abundance and population dynamics of Spodoptera litura F. and Pieris brassicae L. on cabbage, a field experiment was conducted. Larval population of S. litura ranged from 0.56 to 1.57 larvae/plant during 8 January to 12 February 2014 crop season while the highest peak was on 5 February 2014 (1.57 larvae/plant) at 29.5 0C temperature. In case of Pieris brassicae, larval population ranged from 0.58 to1.98 larvae/plant and the highest peak of P. brassicae was also on 5 February. The highest peak was on 5 February 2014 at 96% and 38% relative humidity of both maximum and minimum categories and the highest peak of P. brassicae was on 5 February. There was a strong positive correlation (r = 0.824 and r = 0.920) between population of Spodoptera litura and temperature (maximum and minimum). On the other hand, there was a negative correlation (r = -0.439) between population of S. litura and maximum relative humidity and a strong negative correlation (r = - 0.716) between population of S. litura and minimum relative humidity. The population of Pieris brassicae was positively correlated (r = 0.899 and r = 0.956) with maximum and minimum temperatures. There was a negative correlation (r = -0.443) between population of P. brassicae and maximum relative humidity and a strong negative correlation (r = - 0.645) between population of P. brassicae and minimum relative humidity.SAARC J. Agri., 15(1): 13-21 (2017)